GENEALOGI INTELEKTUAL SYEKH MUHAJIRIN AMSAR ADDARY DALAM PENGEMBANGAN PENDIDIKAN ISLAM DI BEKASI - Hamady, Hanif; Nabil (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
This research discusses the Intellectual Genealogy owned by Sheikh Muhajirin Amsar Addary in the Development of Islamic Education in Bekasi. The method applied in this research is the qualitative historical method.. Sheikh Muhajirin Amsar Addary is a scholar who focuses on education and knowledge. The intellectual genealogy he got while studying came from various types and models of scholars, especially during his time in Mecca and Medina. Sheikh Muhajirin played an active role and made a significant contribution to the development of education in the Bekasi area. This makes him a productive scholar with evidence of as many as 35 books written by him using Arabic. In addition, he also established boarding schools and formal schools from high school to college level to further legitimize his knowledge. The implications given by Sheikh Muhajirin Amsar Addary were so great to the Bekasi community and of course to his students who came to study with him. This is evident from some of Sheikh Muhajirin's students who own boarding schools and continue their knowledge in preaching to the wider community in Indonesia, especially in Bekasi and its surroundings. Sheikh Muhajirin's thoughts on the Prophet's birthday and Rukyatul Hilal are also present in the implications given by Sheikh Muhajirin Amsar Addary.